Observer-Based Adaptive Fuzzy Resilient Control for Fractional-Order Nonlinear State Constrained Systems Subject to Deception Attacks - Zhao, Jipeng; Yang, Guang-Hong (IEEE internet of things journal, 2025)
This article is concerned with the observer-based adaptive resilient control problem of the uncertain fractional-order nonlinear constrained system with unknown sensor deception attacks (SDAs). A new fuzzy state observer is constructed by employing the compromised output signals to estimate the unmeasured states, and the Nussbaum gain function is utilized to cope with the issue of unknown control coefficients caused by the unknown deception attacks. Then, by designing the exponentially-decaying barrier Lyapunov function, the state variables can be constrained in the specified bounds. In view of the fractional-order Lyapunov stability criterion, a novel output feedback resilient control scheme is developed, such that all the signals of the fractional-order nonlinear systems (FONS) are bounded. In contrast to the existing resilient control results in the integer-order nonlinear systems, the designed resilient control scheme not only handles the output feedback resilient control problem of the FONS, but also makes all the states remain in their constraint bounds. Ultimately, a simulation result is used to illustrate the feasibility and the rationality of the designed controller.